Investigating students’ attitude and motivation in learning English as a second language among four higher institutions in Malaysia - Abdul Kadir, Zulida; Abdullah, Rosmahalil Azrol; Palpanadan, Sarala @Thulasi; Zainal Abidin, Siti Sara; Muhammad, Siti Salmiah; Mohamed, Abdullah Adnan (Universitas Diponegoro, 2020)
The aim of this study is to examine the students’ motivation and attitude towards learning English as a second language from four Malaysian higher institutions. A random sampling of 471 respondents participated in this study. Using 28 items instrument, adapted from Gardner’s Attitude/Motivation Test Battery (AMTB), an online questionnaire was distributed in getting the data. Students’ motivational level is found to be high with (M=6.37, SD=0.77, M=6.10, SD=0.82). Additionally, the respondents are having positive attitudes in learning English (M=4.07, SD=0.48). With the findings, it is a hope that this can be a guidance for instructors to design a suitable lesson and approach to be used in the class.